Development of Optical Pressure Sensor for Capillary Refill Time Measurement System - Mohd Sabri, Roziela; Wan Zaki, Wan Suhaimizan; Vajravelu, Ashok; Adon, Mohamad Nazib; Abd Shaib, Mohd Fadzli (Evolution in Electrical and Electronic Engineering, 2022)
Capillary refill time (CRT) refers to the amount of time it takes for a distal capillary bed to regain its color following blanching produced by externally applied pressure. Generally, the CRT is manually observed by the naked eye of the examiner, and the applied pressure impacts it. Therefore, the results are likely to be unreliable and imprecise because of the observer-dependent measurement, and there is no standardization of the actual blanching maneuver. To overcome this problem, this project proposed a CRT with a contact pressure measurement using a flexible tube and optical fiber sensor. A light-emitting diode (LED) and phototransistor circuits were developed for transmitting and receiving light for the CRT and pressure measurement. The signals were transmitted online via a node MCU and processed by the Matlab software through the Thingspeak application. The relationship between the light intensity and the applied pressure was carried out through the experiment using a manual cuff blood pressure system. The results show a nonlinear relationship between the light intensity transmitted by the LED with the corresponding voltage of 0.59 V down to 0.02 V (bright to dimmer). The result from the volunteer’s study shows that voltage detected by the POF sensor increases as pressure increases.  These findings demonstrated that the proposed system could be used for a contact pressure sensor for CRT measurement. The added value of the IoT system makes it useful for online monitoring and will be beneficial to society in the future.